Vortex-Induced Vibration Tests of a Marine Growth Wrapped Cylinder at Subcritical Reynolds Number - Kurian, V.J. (EDP Sciences, 2017)
Vortex Induced Vibrations (VIV) may cause great damage to deep water risers. Estimation of accurate hydrodynamic coefficients and response amplitudes for fouled tubular cylinders subjected to VIVs is a complex task. This paper presents the results of an extensive experimental investigation on in-line and cross-flow forces acting on cylinders wrapped with marine growth, subjected to current at Subcritical Reynolds Number. The drag and lift force coefficients have been determined through the use of the Fast Fourier Analysis methods. The different tests were conducted in the offshore engineering laboratory at Universiti Teknologi PETRONAS (UTP), Malaysia. In this study, a cylinder with outer diameter Do = 27 mm, fixed at top as cantilever beam was used. The in-line and cross-flow forces were measured using VIV Force Totaller (VIVFT). VIVFT is a two degree of freedom (2DOF) forces sensor developed by UTP to measure the VIV forces. The tests were conducted for current velocity varied between 0.118 to 0.59 m/s. The test results suggest that the cylinder wrapped with marine growth has shown an overall increase in drag and inertia coefficients as well as on response amplitudes. © The Authors, published by EDP Sciences, 2017.